2016
DOI: 10.1186/s13046-016-0395-y
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor: role in growth, differentiation and controlling cancer cell development

Abstract: Recent progress in the Nerve Growth Factor (NGF) research has shown that this factor acts not only outside its classical domain of the peripheral and central nervous system, but also on non-neuronal and cancer cells. This latter observation has led to divergent hypothesis about the role of NGF, its specific distribution pattern within the tissues and its implication in induction as well as progression of carcinogenesis. Moreover, other recent studies have shown that NGF has direct clinical relevance in certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 76 publications
0
61
0
2
Order By: Relevance
“…In addition to promoting cancer innervation, neurotrophin-mediated signaling has been shown to directly drive tumor onset and progression [72,74,[80][81][82]. The neurotrophin receptors TRKA, TRKB, and P75/NGFR are expressed by malignant cells in many tumor types, where they inhibit key tumor suppressor mechanisms [82] or directly promote cancer cell proliferation and invasiveness [71,74,80,81,83]. Our results show that ameloblastomas expressed both neurotrophins and neurotrophin receptors.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition to promoting cancer innervation, neurotrophin-mediated signaling has been shown to directly drive tumor onset and progression [72,74,[80][81][82]. The neurotrophin receptors TRKA, TRKB, and P75/NGFR are expressed by malignant cells in many tumor types, where they inhibit key tumor suppressor mechanisms [82] or directly promote cancer cell proliferation and invasiveness [71,74,80,81,83]. Our results show that ameloblastomas expressed both neurotrophins and neurotrophin receptors.…”
Section: Discussionmentioning
confidence: 65%
“…More and more studies support the importance of nerve-derived signals in organ development, homeostasis, regeneration, and in pathological conditions [20,68]. It is well known that most cancers are associated with pain sensation [69], and different studies have reported the expression of neurotrophic factors in many cancer types [70][71][72][73][74]. Only recently a few studies have started shedding light on the fundamental role of innervation for cancer onset and progression.…”
Section: Discussionmentioning
confidence: 98%
“…Substantial interactions have been observed between breast cancer cells and the microenvironment via the nervous system 12,52,53 , namely: (i) breast cancer cells and local immune cells release neurotrophic factors (such as nerve growth factor, NGF) to facilitate nerve invasion 54,55 ; (ii) neurotransmitter secreted by nerve sprouting can act on both breast cancer cells and stromal cells; (iii) repression of neurotrophic factors and receptors can slow down the disease progression 56 ; (iv) once cancer cells penetrate the nerve endoneuria and migrate along the nerve fiber, relapse tends to happen more frequently 57 ; and (v) TNBC has higher death rate than those of the other breast-cancer subtypes, one reason being its high recurrence rates, and the central nerve system (CNS) is one of the most likely location of recurrence in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…It was also used as nanoparticles with paclitaxel for treatment of breast cancer in vivo and in vitro studies [52] This was due to its specific effects on cell proliferation, differentiation, and apoptosis, as well as its low toxicity. On the other hand NGF could induce differentiation rather than proliferation in cancer cell line (pheochromocytoma, glioma, neuroblastoma and pancreatic beta cells ocular glioma [53] .…”
Section: Discussionmentioning
confidence: 96%